Active Video Surveillance Based on Stereo and Infrared Imaging. (21st October 2007) - Pieri Pieri, Gabriele Gabriele; Moroni Moroni, Davide Davide
Abstract : Video surveillance is a very actual and critical issue at the present time. Within this topics, we address the problem of firstly identifying moving people in a scene through motion detection techniques, and subsequently categorising them in order to identify humans for tracking their movements. The use of stereo cameras, coupled with infrared vision, allows to apply this technique to images acquired through different and variable conditions, and allows an a priori filtering based on the characteristics of such images to give evidence to objects emitting a higher radiance (i.e., higher temperature).